STATUS KESUBURAN TANAH PADA LAHAN SAWAH DILINDUNGI YANG BERALIH FUNGSI DI KAPANEWON SEYEGAN, KABUPATEN SLEMAN, DAERAH ISTIMEWA YOGYAKARTA - Hermansyah, Alvin Dwi; Partoyo, Partoyo; Virgawati, Sari (Jurnal Tanah dan Sumberdaya Lahan, 2024)
The conversion of rice fields in Seyegan is suspected to occur due to low soil fertility. This study was conducted to analyze the extent and distribution of conversion of rice fields associated with soil fertility status. This study used a survey method, purposive determination of sample points on rice fields representing the converted rice fields, and soil samples were taken compositely. Data analysis used spatial analysis, graphs, and laboratory tests. The parameters tested were cation exchange capacity (CEC), Base Saturation, potential P2O5, potential K2O, and organic C. Determination of soil fertility status was based on The Technical Guidelines For Soil Fertility Evaluation of Soil Research Center. The results showed that the area of rice fields in Seyegan District in 2015-2022 decreased by 55.26 ha (3.76%), with an average annual decrease of 7.89 ha. The soil fertility status in rice fields converted into settlements was very low to medium, rice fields into dryland and poultry farming were medium, and rice fields into shrubs and factories were low. The limiting factors of soil fertility were CEC and organic C.